(1 → 3)‐β‐d‐glucan enhances the toxicity induced by Bortezomib in rat testis. Issue 3 (20th January 2020) - Akaras, Nurhan; Abuc, Ozlem Ozgul; Koc, Kubra; Bal, Tugba; Geyikoglu, Fatime; Atilay, Hilal; Erol, Huseyin Serkan; Yigit, Serdar; Gul, Murat
Abstract: We aimed to determine the possible effects of the antioxidant agent (1 → 3)‐β‐D‐glucan on bortezomib‐induced rat testis damage. We used five groups of rats; control, (1 → 3)‐β‐D‐glucan (75 mg/kg), bortezomib group, bortezomib + (1 → 3)‐β‐D‐glucan groups (injection of (1 → 3)‐β‐D‐glucan after bortezomib and sacrificed at 48th or 72nd h). The effects of these substances were assessed by measuring the levels of the antioxidant enzymes and LPO, and by performing immunohistochemical analysis with NF‐κB. The histology of testis was evaluated using aniline blue staining. (1 → 3)‐β‐D‐glucan leads to significant reductions in the levels of antioxidant enzymes and increased levels of LPO in testes. Moreover, it increased the NF‐κB immunopositivity significantly in testis, especially in Bortezomib + (1 → 3)‐β‐D‐glucan group at 48th h. The histological changes were observed in the bortezomib and/or (1 → 3)‐β‐D‐glucan groups. Our results demonstrated that testis damage caused by the treatment with bortezomib was not eliminated by (1 → 3)‐β‐D‐glucan and shockingly it increased the damage. Practical applications: The testis damage caused by the treatment with bortezomib was not eliminated by (1 → 3)‐β‐D‐glucan and as a result, β‐1, 3‐(D)‐glucan enhanced the toxicity by leading a decrease in the levels of GSH, SOD, and CAT, thus caused an elevation in the immunoreactivity of NF‐κB and altered the histopathological changes by enhancing the toxic effects of bortezomib. The findings of the previous studies about the antioxidative activity of (1 → 3)‐β‐D‐glucan are controversial. So, it is necessary to consider the cytotoxicity of (1 → 3)‐β‐D‐glucan in testis tissue. Thus, more studies on testis tissue are necessary to confirm that (1 → 3)‐β‐D‐glucan is safe as an antioxidant. Abstract : (1 → 3)‐β‐D‐glucan leads to significant reductions in the levels of GSH, SOD, and CAT and increased levels of LPO in rat testis. (1 → 3)‐β‐D‐glucan enhanced the toxicity by leading a decreased in the levels of antioxidant enzymes, caused an elevation in the immunoreactivity of NF‐κB and an increased the histopathological changes due to enhancing the toxic effects of bortezomib. The testis damage caused by the treatment with bortezomib was not eliminated by (1 → 3)‐β‐D‐glucan, as an antioxidant.